PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-TALK-WRITE PADA MATERI FUNGSI LINEAR SMK MANDIRI PONTIANAK - Meki, Lenisius; Nursangaji, Asep; Munaldus, Munaldus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aimed of this research was to knowed how the effectiveness of cooperative learning model type think-talk-write (TTW) on linear function materials in class XI SMK Mandiri Pontianak. The method used is a pre- experimental research conducted using post test only design, while the subject are 20 the students of class XI SMK Mandiri Pontianak. The result of the data analysis showed that is the ability of teachers to manage learning was in good category an average score of 3.4, student activity during the learning process as a whole is very active with the average percentage of 81.12%, student learning result was complete with an average value of 90.15% and student response during the learning was in very good category with the average percentage of 81.17%. Based on the research findings, it can be concluded that application of cooperatif learning model type think-talk-write (TTW) was effective in teaching a linear function material in class XI SMK Mandiri Pontianak. Keywords: Cooperative Learning Model, Cooperative Learning Type TTW